A Pilot Study on the Safety of a Novel Antioxidant Nanoparticle Delivery System and Its Indirect Effects on Cytokine Levels in Four Dogs - Robinson, Kelsey; Platt, Simon; Bibi, Katherine; Banovic, Frane; Barber, Renee; Howerth, Elizabeth W.; Madsen, Gary (Frontiers in Veterinary Science, 2020)
Acute spinal cord injury consists of a primary, traumatic event followed by a cascade of secondary events resulting in ongoing cell damage and death. There is great interest in prevention of these secondary effects to reduce permanent long-term neurologic deficits. One such target includes reactive oxygen species released following injury, which can be enzymatically converted into less harmful molecules by superoxide dismutase and catalase. Canine intervertebral disc herniation has been suggested as a naturally occurring model for acute spinal cord injury and its secondary effects in people. The aims of this study were to test the safety of a novel antioxidant delivery system in four healthy dogs and to indirectly test effect of delivery via cytokine measurement. All dogs experienced adverse events to some degree, with two experiencing adverse events considered to be severe. The clinical signs, including combinations of bradycardia, hypotension, hypersalivation, pale gums, and involuntary urination, were consistent with complement activation-related pseudoallergy (CARPA). CARPA is a well-known phenomenon that has been reported to occur with nanoparticle-based drug delivery, among other documented causes. Two dogs also had mild to moderate hematologic changes, including elevated alanine transferase and thrombocytopenia, which both returned to normal by day 7 post-administration. Cytokine levels trended downwards over the first 3 days, but many were elevated at measurement on day 7. Intradermal testing suggested catalase as a potential cause for reactions. No long-term clinical signs were observed, and necropsy results revealed no concerning pathology. Additional evaluation of this product, including further characterization of reactions to catalase containing components, dose-escalation, and desensitization should be performed before evaluation in clinically affected dogs.